In Situ Observation of Single Au Triangular Nanoprism Etching to Various Shapes for Plasmonic Photocatalytic Hydrogen Generation - Lou, Zaizhu; Kim, Sooyeon; Zhang, Peng; Shi, Xiaowei; Fujitsuka, Mamoru; Majima, Tetsuro (ACS nano, 2017)
In situ etching of single Au triangular nanoprism (TNP) was successfully monitored by the plasmonic photoluminescence (PL) spectra using single-particle microscopy, which provides clear results to understand the geometric and anisotropic dependence of surface plasmon resonance in Au nanostructures. Various Au nanostructures (TNP, obtuse TNP (O-TNP) and nanodisk) were obtained to synthesize anisotropic Pt–Au as plasmonic photocatalyts for hydrogen generation. Single-particle PL spectra and finite-difference time-domain simulations demonstrate that the Pt-edged Au O-TNP has larger tip area and higher plasmon enhanced electrical field for hot electron transfer and charge separation, leading to more efficient photocatalytic hydrogen generation.